2023
DOI: 10.32322/jhsm.1218420
|View full text |Cite
|
Sign up to set email alerts
|

Association between atherogenic index of plasma and in-hospital mortality in patients with STEMI undergoing primary percutaneous coronary intervention

Abstract: Aim: Dyslipidemia is an established risk factors for cardiovascular disease. Increased triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) levels, and decreased HDL-C levels were associated with increased cardiovascular risk. Recently, comprehensive lipid profile indices derived from these conventional parameters have attracted to attention. Atherogenic index of plasma (AIP) is one of the indices calculated as the logarithm of TG/HDL-C levels and, it is accepted as an alternative and simple marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A significant heterogeneity was found for the no-reflow phenomenon (I 2 = 89.7%, P < 0.001). Three studies analyzed AIP as a continuous variable, which reported an of HR 1.21 (95% CI, 0.72–2.02, P = 0.460), 1.61 (95% CI, 1.12–2.32, P = 0.009), 3.77 (95% CI, 1.34–10.60, P = 0.012), and 13.46 (95%CI, 1.39-129.02; P = 0.025) for cardiovascular death [ 17 ], MI [ 17 ], all-causes death [ 21 ], and stent thrombosis [ 24 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant heterogeneity was found for the no-reflow phenomenon (I 2 = 89.7%, P < 0.001). Three studies analyzed AIP as a continuous variable, which reported an of HR 1.21 (95% CI, 0.72–2.02, P = 0.460), 1.61 (95% CI, 1.12–2.32, P = 0.009), 3.77 (95% CI, 1.34–10.60, P = 0.012), and 13.46 (95%CI, 1.39-129.02; P = 0.025) for cardiovascular death [ 17 ], MI [ 17 ], all-causes death [ 21 ], and stent thrombosis [ 24 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, Refs. [ 16 , 26 , 29 ]) considered AIP as a continuous variable, and found a significant positive correlation between AIP level and risk of all-causes mortality [ 21 ]. This discrepancy may be due to low number of studies and the differences in follow-up duration between the studies.…”
Section: Discussionmentioning
confidence: 99%